POETRY: FOSTERING SELF IDENTITY AND CREATIVE THINKING IN THE EFL CLASSROOM - Ainul Addinna (Universitas Negeri Padang, 2017)
This article describes how poems can effectively be used to foster EFL/ESL students’ self- identity and creative thinking. This study is based on the data gathered from graduate students in English Language Teaching Program of one of state universities in Malang. Twelve students are involved as samples of this study. The participants expressed their perceptions and told their stories after they took English Literature course for a semester. Open-ended questions have used to get the data that allow participants to express their opinion on how their culture identity and culture experience influence them in analyzing the poetry and how poetry could establish their creative thinking, as well as help them find their identity. The results of the written experiences and opinions indicate that some students believe that they have been given an opportunity to work independently through analyzing poems and creating ones. They admitted that their culture experience give an influence in how they analyzing the poetry and this activity was so amusing since they could get new cultural understanding. The participants finally could produce nice and creative poems at the end of the semester based on their own styles.